(untitled) (Jurnal ForestrIndo, 2025)
Modified motorcycles are known as mode for log transportation in remote area. However, these modifications can generate noise. Therefore, it is necessary to understand the noise produced by log transport motorcycles along with its impact on the work environment and workers’ health during skidding activities. The purpose of this research is to determine the level of noise exposure and its impact on the surrounding environment and workers’ health during log transportation activities. The research was conducted using purposive sampling method with the help of a sound level meter and data analysis in the form of contour maps and Wilcoxon non-parametric tests. The results showed that the average noise intensity received by wooden crossbar taxi drivers during skidding activities ranges from 73.4 dB to 101.5 dB, and the average noise intensity in the surrounding environment ranges from 50.6 dB to 101.0 dB. There are noise intensities exceeding the Threshold Limit Value (TLV) at full throttle conditions for both right and left ears. This condition poses a health risk to workers as noise significantly affects workers’ concentration ability, which can be interpreted as: the greater the noise received by workers, the more their concentration ability may decrease.